(untitled) (Bangladesh Journal of Medical Science, 2019)
Introduction: The present research was aimed at studying the usage rate for the complementary and alternative medicine, at identifying its low-consumption and high-consumption methods, and at analyzing the relationship between demographic variables and the usage rate of this medicine among the people who visited the non-conventional medical centers in Shiraz, Iran. Methods: This research is an analytical-cross-sectional study in which 800 people have been visited 6 non-conventional medical centers in July 2016; having gained their satisfaction, they were studied by method of complete enumeration. The data were collected using a researchermade questionnaire and analyzed through SPSS. Result: In this study, 68% of visitors used the complementary and alternative medicine in medium rate. The high-consumption kind includes the Natural products, the Movement-based approaches and the Traditional treatments. The low-consumption kind includes the Energy-based treatments and whole medical system. The demographic variables such as age, gender, ethnicity, education, birth place and occupation were in relation with the usage rate of complementary and alternative medicine. Conclusion: The healthy people have tended to use the complementary and alternative medicine as a part of their healthy lifestyle. The high-consumption strands had origin in the culture and tradition of a society and they are easily available. The low-consumption strands include the methods that the people were less familiar with them; these strands have limited accessibility and the higher costs. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.294-302